FAKTOR-FAKTOR YANG MEMPENGARUHI PENURUNAN POPULASI TERNAK KAMBING PERANAKAN ETAWA (Studi Kasus pada Kelompok Ternak Sukapala Kecamatan Kawalu Kota Tasikmalaya) - Ane Novianty; Benizar M. Andrie (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Etawa breeders are faced with a situation with a limited amount of capital, production factor and knowledge in an effort to achieve their goal. This condition causes the decline of PE goat’s population year by year even though the product produced has a strategic opportunity in the market. The purpose of this study is to determine the factors that influence the decline of PE goat’s population in Sukapala herd. The study is carried out in Sukapala herd, Kawalu district, Tasikmalaya city  which consists of 9 people by using a case study method. The factors that influence the decline of PE goat’s population based on multiple linear regression test are capital (X1), treatment and maintenance system (X2), seed’s quality (X3), and livestock breeds quality (X4). Based on the results of partially and simultaneously test, the four independent variables influence significantly in the decline of PE goat’s population and have a negative effect.